Risk Management Strategies in the Global Business Environment: Analysis of Complex Dependencies and Effectiveness of Measures - Baldzhy, Maryna D.; Балджи, Марина Дмитрівна; Kateryna, Khavrova; Olga, Guseva; Alona, Goloborodko; Anastasia, Artyomova (My University, 2023)
The study investigates risk management strategies within the global business environment, focusing on the analysis of intricate dependencies and the efficacy of corresponding measures. The significance of this research arises from the contemporary reality wherein the business environment contends with a multitude of influential factors capable of altering the organizational dynamics of the business realm. Consequently, enterprises and companies must cultivate preparedness for diverse factors that threaten their sustained viability. The article deliberates on risk management strategies within the global business environment, emphasizing the analysis of complex dependencies and the effectiveness of implemented measures. The significance of risk management in the current stage of development is delineated. The essence of risk management strategies is explicitly defined, and factors that possess the potential to impact the operational dynamics of enterprises adversely are systematically examined. The paper outlines various methods of risk management planning, including acceptance, transfer, avoidance, and reduction. The specific application nuances of each method are expounded upon. Additionally, the interrelationship between risk management methods and strategies is delineated, providing clarity on their respective roles and contributions. The examination of risk management strategies encompasses the analysis of specific approaches, namely the one percent strategy, stop-loss and take-profit order strategy, diversification and hedging, exit strategy, and research strategy. The study identifies the predominant domains wherein each strategy is frequently employed, elucidating their fundamental characteristics and discerning their impact on alterations within the company’s operations. Furthermore, illustrative examples of these strategies are provided to enhance understanding. The summary of risk management strategy implementation in the enterprise’s activities is presented, elucidating the principal aspects, stages, and procedural framework. The determination of the impact of implementation on the company’s operations and its capacity to mitigate risks is systematically addressed.
Risk Management Strategies in the Global Business Environment: Analysis of Complex Dependencies and Effectiveness of Measures / M. Baldzhy, K. Khavrova, O. Guseva, A. Goloborodko, A. Artyomova // Economic Affairs. – 2023. – Vol. 68, № 4. – Р. 2095-2103. DOI: 10.46852/0424-2513.4.2023.20
Keywords: Business environment; corporate environment; enterprise; implementation of risk management strategy; methods of risk management planning; risk management strategy; Research Subject Categories::SOCIAL SCIENCES